(untitled) (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY Cystic fibrosis is the most common genetic disorder in Caucasians. The combination of the cystic fibrosis transmembrane conductance regulator (CFTR) corrector lumacaftor / potentiator ivacaftor (LUM/IVA) has been shown to increase forced expiratory volume in 1 second (FEV1) moderately, but predominantly reduce acute exacerbation rate (AER) in Phe508del homozygous cystic fibrosis patients; however, patients with FEV1 <40% predicted were excluded from studies. We used LUM/IVA on a “compassionate use” basis in cystic fibrosis patients with end-stage pulmonary disease. Our aim was to evaluate if this patient cohort tolerates LUM/IVA treatment and if there is clinical stabilisation. Lung transplantation (LTX) is the ultimate treatment option for these patients despite maximal therapy. If LTX candidates stabilise clinically, conditions for LTX, when it is indicated, improve. This is particularly important in countries such as Switzerland with a low organ donation rate and long waiting times for suitable donor organs. METHODS We included all patients from the Adult Cystic Fibrosis Centre at the University Hospital Zurich with Phe508del homozygous genotype and a predicted FEV1 <40% or being evaluated or already listed for LTX. Clinical outcome data comprised AER, 6-minute walking distance (6-MWD), FEV1, forced vital capacity (FVC), mid-expiratory flow (MEF 25–75%), sweat chloride, body mass index (BMI) and quality of life. Respiratory-related adverse events (RAEs) were recorded. LUM/IVA treatment was initiated at a low dose and the dose increased stepwise. RESULTS Twenty patients were on trial with LUM/IVA; at the cut-off date, 6-month follow-up was complete for 10 patients. RAEs were severe and occurred early. The dropout rate due to RAE or lack of clinical success was 20%. Median AER decreased from 2.5 in the 6 months pre-treatment to 1 during the observation period. FEV1 increased from 32 to 34.5% predicted, p = 0.292. The 6-MWD increased by a median 33 m (p = 0.6086). Sweat chloride decreased significantly by a median of 25 mmol/l (p = 0.0003). Median BMI increased from 19 to 19.9 kg/m2 (p = 0.1488). At the cut-off, three previously listed patients were paused on the transplant waiting list. CONCLUSION Phe508del homozygous cystic fibrosis patients with end-stage pulmonary disease tolerated LUM/IVA, although RAEs occurred early and were severe. This positive finding was probably due to the stepwise dose increases. There was clinical benefit mainly from reduction in AER and stabilisation of lung function. We propose that all suitable Phe508del homozygous cystic fibrosis patients with end-stage pulmonary disease should have a trial of LUM/IVA treatment in experienced centres.